Rasional Emotive Behavior Therapy (REBT) Untuk Mengurangi Adiksi Game Online Pada Siswa Generasi Z - Sri Muliya Hidayani; Luk Luk Yata Lalak Muslimin; I Nyoman Rajeg Mulyawan (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Online game addiction is a chronic and compulsive behavior to satisfy oneself and cause problems in the education world of generation Z. This research aims to determine the effect of the effectiveness of the Rational Emotive Behavior Therapy (REBT) approach through group counseling services on efforts to reduce online game addiction for Z generation students. class VII B SMP 1 Denpasar. This type of research is a quantitative experiment using a one-group pretest and posttest research design involving 5 generation Z students of class VII B SMP 1 Denpasar who were detected to be addicted to online games. The method applied to collect data in this research used questionnaires and observation. The results of this research with a significance value of 0.001<0.005 can be concluded that group counseling services are effective in reducing online game addiction.